2015 ASEE Annual Conference and Exposition Proceedings
DOI: 10.18260/p.24748
|View full text |Cite
|
Sign up to set email alerts
|

Student and Teaching Assistant Perspectives on Characteristics of an Effective Teaching Assistant

Abstract: B.A. Liberal Studies and M.A. Education from Vanguard University of Southern California. M.S. Civil Engineering Texas Tech University. Currently pursuing a PhD in Civil and Environmental Engineering with focus on the biological treatment of waste water for re-use applications. I am passionate about both engineering and education. I am specifically interested in student motivation, formative assessment, service learning, and the influence of the affective domain. Daniel Baldwin Maeghan Marie Brundrett, Texas Te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…From a small sample size of 6 graduate TAs at Texas Tech University, survey results suggested that graduate teaching assistants view preparedness, fair grading, and enthusiasm as the most important aspects of being an effective TA, while topics such as "treats all students with respect", "encourages students to ask questions", "cares about student success", and "is an expert in the content area" were the lowest traits on the ranked list [12], indicating that TAs are not being pushed to view their UGTA role as a trial for a potential career in academia where the goal is to focus on the students. Results from a study performed by Weidert et al show many selfreflected benefits of an undergraduate teaching assistant experience, including confidence, team abilities, and personal insight [13].…”
Section: Literature Reviewmentioning
confidence: 99%
“…From a small sample size of 6 graduate TAs at Texas Tech University, survey results suggested that graduate teaching assistants view preparedness, fair grading, and enthusiasm as the most important aspects of being an effective TA, while topics such as "treats all students with respect", "encourages students to ask questions", "cares about student success", and "is an expert in the content area" were the lowest traits on the ranked list [12], indicating that TAs are not being pushed to view their UGTA role as a trial for a potential career in academia where the goal is to focus on the students. Results from a study performed by Weidert et al show many selfreflected benefits of an undergraduate teaching assistant experience, including confidence, team abilities, and personal insight [13].…”
Section: Literature Reviewmentioning
confidence: 99%